Mediating role of motivation on competencies and job performance among agriculture extension workers in Peninsular Malaysia - Umar, Sulaiman (2018)
Climate change is threatening agriculture, a sector upon which humanity depends for survival. Efficient extension and advisory services are vital in disseminating appropriate climate-smart innovations. Hence, there is need to assess the predictors of job performance of extension workers. The purpose of this study is to determine the prediction and mediation effect of motivation in the relationships between job performance, competencies, and perceived organizational support among extension workers delivering climate-smart agriculture advisory services in Malaysia. A review of theories revealed many overlapping constructs and relationships in the framework of factors affecting job performance. This study identified the most relevant of those, conceptualized them and designed a conceptual framework depicting the inter-relationships. The study employed the quantitative approach and descriptive correlational design. A sample of 350 extension workers in 11 states of Peninsular Malaysia was randomly selected. The data obtained using a self-administered questionnaire was analysed using descriptive statistics, Pearson product moment correlation, multiple linear regression and structural equation modelling. Demographic profiling indicated that majority of the extension personnel are middle-aged men that were employed in the agricultural assistants’ cadre. Significant correlation (p < 0.001) existed between each pair among the latent constructs except between motivation and core extension competency. The multi-model analysis conducted in this study revealed that the mediated model is better than the direct model in explaining the inter-relationships. It had an R2 of 0.45 against 0.22 of the direct model. This implies that the multivariate analysis involving intermediation is a better representation of the antecedents of job performance. The final model achieved all categories of fit indices (Relative Chi-Sq. = 3.146; CFI = 0.908; RMSEA = 0.079; RMR = 0.047). It indicated that job performance is significantly affected by the workers’ competence, motivation and perceived organizational support with direct positive relationships in all cases. Meanwhile, indirect relationship using motivation as a mediator showed full mediation of motivation on the relationship between POS and job performance and partial mediation on the relationship between CSA advisory competence and job performance. It should be noted that both core and specialized competencies are vital to effective extension service delivery. In this study, not only do they correlate but aspects of both (in form of planning and evaluation competency and CSA competency respectively) combined to influence the performance of extension workers in the delivery of CSA technologies and practices. Conclusively, motivation has proven to be a significant determinant of performance. It also mediates the association between other antecedents and performance. To adapt to the menace of climate change affecting farmers’ food security, productivity and livelihood, there is need for robust extension service delivered by competent, motivated and organizationally supported agents. The final model developed in this study could serve as a blueprint for achieving high performance in such service.